Trace Class and Lidskiĭ trace formula in Kaplansky–Hilbert modules - GÖNÜLLÜ, UĞUR (My University, 2014)
In this paper, we introduce and study the concepts of the trace class op-erators and global eigenvalue of continuous Λ-linear operators in Kaplansky−Hilbertmodules. In particular, we give a variant of Lidski˘ı trace formula for cyclically com-pact operators in a Kaplansky−Hilbert modules.
Keywords: Kaplansky-Hilbert module; cyclically compact operator; global eigenvalue; trace class; Lidskiĭ trace formula